PENGARUH AUDIT INTERNAL, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PT. BANK NEGARA INDONESIA (PERSERO) TBK. - Muhammad Farhan Adhyasa (2023)
This study aims to determine the effect of internal audit and human resource competence on the quality of PT. Bank Negara Indonesia (Persero) Tbk. The sample of this research are employees of PT. Bank Negara Indonesia (Persero) Tbk. the Budgeting and Financial Control (PKU) division, and the Internal Audit Unit (SAI) division. The sample in this study were 30 respondents from 2 divisions at PT. Bank Negara Indonesia (Persero) Tbk. The data used in this study is primary data, namely giving questionnaires to the BCV division. Testing the research hypothesis using Multiple Linear Regression Analysis using the Statistical Program and Service Solution (SPSS) version 26 and a significance level of 5%. The results of the research partially show that the internal audit variable and the human resource competency variable have a significant effect on the quality of the financial statements of PT. Bank Negara Indonesia (Persero) Tbk.